The MWA long baseline Epoch of reionisation survey—I. Improved source catalogue for the EoR 0 field. (29th November 2021) - Lynch, C. R.; Galvin, T. J.; Line, J. L. B.; Jordan, C. H.; Trott, C. M.; Chege, J. K.; McKinley, B.; Johnston-Hollitt, M.; Tingay, S. J.
Abstract: One of the principal systematic constraints on the Epoch of Reionisation (EoR) experiment is the accuracy of the foreground calibration model. Recent results have shown that highly accurate models of extended foreground sources, and including models for sources in both the primary beam and its sidelobes, are necessary for reducing foreground power. To improve the accuracy of the source models for the EoR fields observed by the Murchison Widefield Array (MWA), we conducted the MWA Long Baseline Epoch of Reionisation Survey (LoBES). This survey consists of multi-frequency observations of the main MWA EoR fields and their eight neighbouring fields using the MWA Phase II extended array. We present the results of the first half of this survey centred on the MWA EoR0 observing field (centred at RA (J2000) $0^h$, Dec (J2000) $-27^{°}$ ). This half of the survey covers an area of 3 069 degrees $^2$, with an average rms of 2.1 mJy beam –1 . The resulting catalogue contains a total of 80 824 sources, with 16 separate spectral measurements between 100 and 230 MHz, and spectral modelling for 78 $%$ of these sources. Over this region we estimate that the catalogue is 90 $%$ complete at 32 mJy, and 70 $%$ complete at 10.5 mJy. The overall normalised source counts are found to be in good agreement with previous low-frequency surveys at similar sensitivities. Testing the performance of the new source models we measure lower residual rms values for peeled sources, particularly for extended sources, in a set of MWA Phase I data. The 2-dimensional power spectrum of these data residuals also show improvement on small angular scales—consistent with the better angular resolution of the LoBES catalogue. It is clear that the LoBES sky models improve upon the current sky model used by the Australian MWA EoR group for the EoR0 field.